Sandwich- Course in Higher Education and Entrepreneurship Awareness: Case of the Graduates from University Apprenticeship Training Centre, Corsica (Global Journal of Human-Social Science, 2016)
Long limited to level V and VI courses often intended for students who failed academically sandwich courses radically tarnish this typical image and gradually gain ground in higher education Increasing the average graduation rate ensuring a better vocational integration this training system has proven to be a path to excellence and a pathway to employment Sandwich courses in higher education seems to stay the course in a gloomy social and economic context especially among young graduates Such a situation is first due to learning reasons graduation rate promotion majors but ultimately sandwich courses pull out of the game in the workforce market by potentiating concurrently occupational integration graduates employability and entrepreneurship awareness CFA Univ Corsica a regional leader in sandwich courses after completion of secondary studies 60 of students in Corsica is the structuring player in the island economy insofar as almost 8000 island companies will have to be sold within the next 10 years
Keywords: higher education-sandwich course- occupational integration - entrepreneurship awareness - business creation and takeover